TEKNIK NARASI DALAM TIGA NOVEL KARYA WILLIAM FAULKNER - Rido Budiman (Fakultas Komunikasi, Sastra, dan Bahasa, 2010)
In this research I discuss the narration technique in three of William Faulkner works Absalom, Absalom!, Light in August, and As I Lay Dying. Faulkner uses multiple narrators in those three works. The aim of my thesis writing is to discuss how the narration technique with multiple narrators is used in those three novels. Faulkner applies multiple narrators in a form of narration that completes each other in certain modes of narration hence the readers could understand the story of each novel in many different point of views. There are several modes of narration that Faulkner applies such as supporting narration mode, negating narration mode, questioning narration mode, and dominance narration mode